IMARAH ISLAMIAH: THE IMPLIMENTATION IN MODERN JEWELLERY DESIGN - Abu Bakar Abdul Aziz; Mohd Faiz Jalaludin; Muhammad Shafiq Muda; Mohd Hakim Mohd Sharif; Adib Mohd Hasan (Journal of Islamic, Social, Economics and Development, 2023)
The Arabic phrase ‘Imarah Islamiah’ refers to Islamic architecture. This study primarily focuses on the seven principles of Islamic architecture. This research was developed based on a few problem statements. First, the lack of awareness and responsibility as Muslims in the creative industry especially in the product design field. The next problem is inadequate knowledge among young pioneer designers on the application of elements in Islamic art and architecture. The researchers have aimed at three objectives, first is to make the elements of Islamic architecture as a reference in producing jewellery designs. Second, to produce jewellery design that complies with the Islamic Architecture element and principles and the third objective is to preserve the Islamic lifestyle as the continuous design fundamentals. Islamic architectural components and principles have been integrated into modern product design through the enhancement of competitive design and the exploration of a number of alternative designs. Modern jewellery is influenced by Islamic architectural details and ideas with a focus on design aesthetics and contemporary demands. In order to create the product design, the exploration process is employed, which involves making personal observations on relevant study topics, such as related technologies, and collecting secondary data. The methodology includes aesthetic, usability, and technological design elements in the percentage. In order to properly harness the potential of Islamic architectural features in product design, the discoveries that suggest optimal design are crucial. The ramifications of the findings were explored in relation to the focus on product design criteria ‘Imarah Islamiah’ which was tied to the title. This study has found that the structural form of the ‘Muqarnas’ one of the most attractive Islamic architectural ornaments, may be developed into a wide range of competitive product designs. Additionally, Islamic architectural features have been well-known for centuries and can be employed as the trademark of modern Malaysian product design.